Pengembangan Lembar Kerja Berbasis Collaborative Argumentation Learning Model (CALM) Untuk Meningkatkan Keterampilan Argumentasi Ilmiah Materi Pemanasan Global - Ashfy, Aulia Camila; Admoko, Setyo (Universitas Negeri Surabaya, 2024)
Scientific argumentation plays an important role in learning. The facts obtained show that students' argumentation skills are still relatively low. Difficulty building arguments is caused by students having difficulty understanding the concept of argumentation, difficulty using relevant evidence to support arguments, and difficulty constructing logical arguments. The low level of students' ability to argue is also due to conventional learning activities and not yet practicing argumentation skills. So we need learning models and tools that can train students to develop scientific argumentation skills, namely worksheets based on the Collaborative Argumentation Learning Model (CALM). This development research aims to describe the validity of CALM-based worksheets to improve scientific argumentation skills on global warming material. This research uses a 4-D development model with 4 stages, namely define, design, develop and disseminate. However, this research is limited to the develop stage. The CALM-based worksheet to improve students' scientific argumentation skills on global warming material that has been developed is included in the very valid category in terms of content and construction aspects. This is based on the worksheet validity results of 96% in the very valid category, so that the worksheet developed is very valid and suitable for use in learning activities.